2016
DOI: 10.2147/ijn.s111748
|View full text |Cite
|
Sign up to set email alerts
|

Proretinal nanoparticles: stability, release, efficacy, and irritation

Abstract: Despite many potent biological activities, retinoids such as retinoic acid (RA) and retinal possess dose-related broad side effects. In this study, we show that this problem, which has been unsolvable for a long time, can be tackled through a controlled release strategy in which retinal is continuously delivered to the skin via sustained release from proretinal nanoparticles. The water dispersible proretinal nanoparticles are stable when kept in water at neutral pH and at room temperature for 8 months under li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Compared to UA, other actives employed to counter skin aging have either a less favourable safety profile or more limited range of beneficial effects. Retinol is a commonly used active known to increase collagen production, reduce fine lines, wrinkles and to improve photoaging 5,19 . However, retinol increases cell turnover in skin, which results in peeling and dry and flaky effect on skin.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to UA, other actives employed to counter skin aging have either a less favourable safety profile or more limited range of beneficial effects. Retinol is a commonly used active known to increase collagen production, reduce fine lines, wrinkles and to improve photoaging 5,19 . However, retinol increases cell turnover in skin, which results in peeling and dry and flaky effect on skin.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their size and penetration powers, liposomes hold immense importance and are by far the highest-used material for retinoid formulations. Studies conducted by the Korean Society [30,103] have shown that retinol when incorporated into lamellar liposomes exhibits a slower degradation and an increased shelf life as compared to its non-liposomal counterparts. Studies conducted by [104] use multi-layered liposomal delivery technology which incorporates 0.5% retinol coupled with niacinamide and Terminalia chebula [104].…”
Section: Liposomesmentioning
confidence: 99%
“…Vitamin A (retinoids, including retinal, retinol, and retinoic acid) is an essential vitamin in the human body. While retinoic acid and retinal exhibit pharmacological effects, such as treating acne and psoriasis, , their clinical application is limited due to local irritation . In contrast, retinol finds widespread use in food, beverages, skincare, and health products, owing to its physiological functions: the promotion of growth and reproduction, maintenance of visual function, stabilization of epithelial tissue, and regulation of immune function .…”
Section: Introductionmentioning
confidence: 99%